Successful Businesses and the Fall into Poor Performance - A Case Study Analysis of The Retail Industry - Clarkson, James (2009)
Using the resource-based view of the firm, this study examines how and why successful companies can fall into poor performance. The project uses a qualitative research design, specifically a case study analysis of six high to low and four consistently high performing firms, which were systematically chosen within the retail industry. Data for each case was collected through trade publications, annual reports, academic journals, newspaper articles and financial data from the FAME database. Each of the findings from each case were compared and contrasted in order to gain an answer to the research question. Results of the cross-case analysis indicated, even with the presence of external factors affecting business performance, that even though each firm had individual strategic resources, it was those firms who used those resources in the most efficient way which were the most likely to remain consistently high in their performance levels.